SISTEM PAKAR DETEKSI PENYAKIT GINJAL BERBASIS MOBILE ANDROID - Malahina, Edwin Ariesto Umbu (HOAQ (High Education of Organization Archive Quality) : Jurnal Teknologi Informasi, 2019)
Non-communicable diseases are diseases with the highest mortality where the mortality rate for this disease is 73%. Kidney disease is one of the non-communicable diseases in which disorders that occur in the kidney, are in two organs shaped like red beans on both sides of the lower back, precisely below the rib cage. Kidney disease taken in this study were 7 diseases namely kidney stone, kidney failure, kidney cancer, acute kidney failure, kidney infection, kidney cysts and polycystic kidney disease. Where in detecting the symptoms of this disease, a truly expert system and expert data are needed, and the implementation of the system makes it easier to develop alternative services using an Android smartphone where users will choose symptoms to be detected early, of course only specifically for detecting kidney diseases. This system will be easy to apply and use because it has only one display. And this system has run well according to the rules of symptoms and diseases that are given or applied.